Healthy Eating: Nutrition and Diabetes - Linda B. Bobroff; Jennifer Hillan; Emily Minton (EDIS)
Revised! FCS8612, a 2-page illustrated fact sheet by B. Bobroff, Jennifer Hillan, and Emily Minton, provides tips for a healthy diet that can help control diabetes and reduce the risk of complications. Published by the UF Department of Family Youth and Community Sciences, December 2009.